Gender disparity in access to advanced therapies for patients with Parkinson’s disease: a retrospective real-word study - Maccarrone, Giuseppe; Saporito, Gennaro; Sucapane, Patrizia; Rizi, Chiara; Bruno, Federico; Catalucci, Alessia; Pistoia, Maria Letizia; Splendiani, Alessandra; Ricci, Alessandro; Di Cesare, Ernesto; Rizzo, Marina; Totaro, Rocco; et al. (Frontiers in Neurology, 2024)
Background Gender differences in the access to advanced therapies for Parkinson’s disease (PD) are poorly investigated. Objective The objective of this study was to investigate the presence of any gender disparity in the access to advanced therapies for PD. Design Retrospective study. Methods Data from patients with consistent access to the Parkinson’s and Movement Disorder Center of L’Aquila over the last 10-year period were screened. Patients selected for advanced therapies were included. Results Out of 1,252 patients, 200 (mean age ± SD 71.02 ± 9.70; 72% males; median Hoen Yahr level: 3, minimum 1 maximum 5) were selected for advanced therapies: 133 for Magnetic Resonance guided Focused Ultrasound (MRgFUS) thalamotomy (mean age ± SD 70.0 ± 8.9; 77% males), 49 for Levodopa/Carbidopa Intestinal Gel (LCIG) infusion (mean age ± SD 74.3 ± 11.4; 59% males), 12 for Deep Brain Stimulation (DBS) (mean age ± SD 71.2 ± 6.3; 75% males), and 7 for Continuous Subcutaneous Apomorphine Infusion (CSAI) (mean age ± SD 69.7 ± 5.5; 43% males). No sex differences were found in relation to age (MRgFUS group: males vs. females 70.2 ± 8.9 vs. 70.8 ± 8.9, p-value = 0.809; LCIG group: males vs. females 73.5 ± 13.0 vs. 75.5 ± 8.5, p-value = 0.557; DBS group: males vs. females 77.2 ± 8.1 vs. 67.3 ± 8.6, p-value = 0.843; CSAI group: males vs. females 73.3 ± 4.0 vs. 67.0 ± 5.2, p-value = 0.144) and disease duration (MRgFUS group: males vs. females 8.3 ± 4.4 vs. 9.6 ± 6.7, p-value = 0.419; LCIG group: males vs. females 14.5 ± 5.81 vs. 17.3 ± 5.5; p-value = 0.205; DBS group: males vs. females 15.0 ± 9.6 vs. 15.5 ± 7.7, p-value = 0.796; CSAI group: males vs. females 11.7 ± 3.7 vs. 10.3 ± 3.7, p-value = 0.505). Conclusion The predominance of males is higher than that expected based on the higher prevalence of PD in men. Women are less confident in selecting advanced therapies during the natural progression of their disease. Factors accounting for this discrepancy deserve further investigation.